The Effect of Time Management, Student Creativity and Learning Motivation on Student Learning Outcomes Case Studies on Economics - Dessy Rahmayanti; Siti Nurjanah; Siti Fatimah Zahra (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
This study aimed to analyze the effect of time management, student creativity and learning motivation on student learning outcomes at SMAN 62 Jakarta in the subject of Economics. The method used in this research was descriptive quantitative with Path Analysis approach. The population in this study were all students of class XI science and social studies at SMAN 62 Jakarta, totally 239 students. Population members taken as a sample were 120 respondents. The sampling technique was proportional stratified random sampling. Data was collected by using a questionnaire and distributed via google forms to 120 students of class XI science and social studies at SMAN 62 Jakarta. This study revealed that: (1) time management had a positive and significant effect on learning outcomes, (2) student creativity had a positive and significant effect on learning outcomes, (3) learning motivation had a positive and significant effect on learning outcomes, (4) time management, student creativity and motivation learning together had a positive and significant effect on learning outcomes.